Regional Impact of Cote D'Ivoire's Sociopolitical Crisis : An Assessment - Engmann, Dorothy (IMF Working Papers; Working Paper ;, 2003)
This paper evaluates the impact of the sociopolitical crisis in Cote d'Ivoire on the economies of its neighbors. Using a nonsubjective weighted index of regional instability in cross-country time-series regressions, it shows that the increase in regional instability caused by domestic instability in Cote d'Ivoire had a negative effect on the growth performance of its most direct neighbors, but no significant effect on the subregion as a whole including the West African Economic and Monetary Union (WAEMU). The paper also examines the channels through which such spillover effects took place.